2021
DOI: 10.3390/polym13152464
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Functionalized Photosensitive Polymeric Nanocarriers

Abstract: The synthesis of light-responsive nanocarriers (LRNs) with a variety of surface functional groups and/or ligands has been intensively explored for space-temporal controlled cargo release. LRNs have been designed on demand for photodynamic-, photothermal-, chemo-, and radiotherapy, protected delivery of bioactive molecules, such as smart drug delivery systems and for theranostic duties. LRNs trigger the release of cargo by a light stimulus. The idea of modifying LRNs with different moieties and ligands search f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 191 publications
(331 reference statements)
1
21
0
Order By: Relevance
“…Although nanocarrier surfaces can be functionalized with a high ligand density due to their high surface-area-to-volume ratio, the density needs to be carefully tuned to optimize the balance between diffusion, uniform distribution, penetration depth, and binding affinity [ 32 ]. Functionalization can be achieved by various conjugation methodologies recently reviewed by our group [ 58 ]. Conventionally, the ligands used for active targeting are specific to bind to overexpressed receptors in tumor cells compared to healthy cells (a mechanism known as active tumor targeting).…”
Section: Influence Of Biological Barriers On Drug Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although nanocarrier surfaces can be functionalized with a high ligand density due to their high surface-area-to-volume ratio, the density needs to be carefully tuned to optimize the balance between diffusion, uniform distribution, penetration depth, and binding affinity [ 32 ]. Functionalization can be achieved by various conjugation methodologies recently reviewed by our group [ 58 ]. Conventionally, the ligands used for active targeting are specific to bind to overexpressed receptors in tumor cells compared to healthy cells (a mechanism known as active tumor targeting).…”
Section: Influence Of Biological Barriers On Drug Delivery Systemsmentioning
confidence: 99%
“…To cite an example, click chemistry conjugation involves generating building blocks by adjoining small units with heteroatom links (C–X–C) in between [ 164 ] Other functionalization strategies employ different functional groups, such as thiol and vinyl sulfone [ 165 ], hydroxyl and amine [ 166 ], and aldehyde [ 167 ], present on the targeting ligand of the polymersome surface. For more details, please refer to our recent review on the functionalization of photosensitive nanocarriers [ 58 ].…”
Section: Polymersomes As a Platform For Anticancer Therapeutic Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocarriers are synthesized with free functional groups with a positive or negative net charge, porosity, and adsorption characteristics on their surface for functionalization, targeting biomolecules via covalent linking, adsorption, and π-π interaction strategies, promoting specific interactions with the target cells [242][243][244]. Fernández and Orozco summarized different chemistries for functionalizing photosensitive nanocarriers in a recent review [245].…”
Section: Functionalization Of Phototriggered Nanocarriers For Targeting Cellsmentioning
confidence: 99%
“…The polymer-based nanocarriers are more often considered as carrier molecules for various drug delivery applications, including PDT. Polymer-based nanocarriers can alter their surface chemistry to functionalize the specific targeting moieties (ligands or antibodies), which helps to facilitate site-specific or targeted drug delivery to the site of action [37,38]. Li et al (2021) recently reported the use of biocompatible nanocomplex for cancer therapy-the synthesized 5,10,15,20-tetrakis (4-aminophenyl) porphyrin (TAPP) and Fe3 + -loaded PEGylated polygalacturonic acid nanocomplex increased the 1 O 2 upon 760 nm laser irradiation, and exhibited cytotoxic effects in B16 melanoma cells [39].…”
Section: Polymer-based Nanocarriersmentioning
confidence: 99%